DAMPAK PEMBELAJARAN DARING BAGI GURU SD/MI DI KECAMATAN WIDODAREN NGAWI - Satriyawan, Aziz Nuri; Sriyanto, Agus; Salikah, Sri Hidayatus (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
Since the beginning of 2020, Indonesian has been hit by the Covid-19 Pandemic, which has bad an impact on various sectors, including education, especially in the Ngawi region of East Java. Various efforts made by the Government include limiting community activities. The purpose of this study is to present information related to teacher perceptions regarding the challenges of implementing online learning at home due to the impact of the COVID-19 pandemic. Information on teacher perceptions regarding the challenges of implementing online learning uses case studies with a qualitative approach. The informants consisted of seven SD/MI teachers in the Widodaren sub-district, Ngawi Regency, Eats Java. The result of this study indicate that there is uneven socialization related to online learning so that the process of learning activities can be said to be less than optimal, the delivery of material is less than optimal, the burden of buying internet quotas, internet connections thet sometimes become sluggish learning styles that tend to be visual, and the teacher’s lack of flexibility in controlling student activities